Микропроцессоры: системы программирования и отладки - Мясников В. А. Владимир Александрович; Игнатьев М. Б. Михаил Бортсович; Кочкин А. А. Андрей Агафенгелович; Шейнин Ю. Е. Юрий Евгеньевич; Игнатьев М. Б. Михаил Борисович (Москва, Энергоатомиздат, 1985)
Авторы указаны в конце книги.